O estatuto da imagem fotográfica: uma abordagem da Bibliotheca de Rosângela Rennó - Silva, Edison Silvestre Petenussi (2009)
This present work has as objective a discussion about the statute of photographic image, its uses and characteristics from an analysis of the work of plastic artist Rosângela Rennó and from the approach of two philosophers, Walter Benjamin and Roland Barthes. It was presented a brief historic of the birth of photography and after, an introduction of the ideas of Walter Benjamin, specially his considerations about the work of art and its technical reproduction. Subsequently, it was introduced the considerations about photography developed by French philosopher Roland Barthes in his famous book Camera Lucida . It was examined the work of plastic artist Rosângela Rennó in the light of these philosopher s works. The analysis is about a specific work, Bibliotheca a compiled images redeemed by artist and reused as support for the development of her artistic universe. The issue of photography as a possibility of memory rescue, the massification of photographic images and the appropriation of existing images resignified in the art guided this dissertation